2019
DOI: 10.1155/2019/6362835
|View full text |Cite
|
Sign up to set email alerts
|

Research on Instability Boundaries of Control Force for Trajectory Correction Projectiles

Abstract: The balance of stability and maneuverability is the foundation of the trajectory correction projectile. For the terminal correction projectile without an attitude feedback loop, a larger control force is expected which may cause an instability. This paper proposes a novel method to derive instability boundaries for the control force magnitude. No additional coordinate system is needed in this method. By introducing the concept of angular compensation matrix, the exterior ballistic linearized equations consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 29 publications
(32 reference statements)
0
8
0
Order By: Relevance
“…For a 15 kg, 105 mm projectile, not more than 40N (0.34 g) could be applied. Li et al 29 continued this work and concluded that the same projectile would remain stable provided F c 2 [ À 35.48, 58.33]. The provided F c is within the limits defined by these frameworks; projectile stability is ensured by satisfying the gyroscopic stability criterion.…”
Section: Quasi-dynamic Guidance Law Formulationmentioning
confidence: 96%
See 1 more Smart Citation
“…For a 15 kg, 105 mm projectile, not more than 40N (0.34 g) could be applied. Li et al 29 continued this work and concluded that the same projectile would remain stable provided F c 2 [ À 35.48, 58.33]. The provided F c is within the limits defined by these frameworks; projectile stability is ensured by satisfying the gyroscopic stability criterion.…”
Section: Quasi-dynamic Guidance Law Formulationmentioning
confidence: 96%
“…This section describes the seven DOF dynamic model of the DSP, which has previously been used to investigate DSPs 21,[27][28][29] and is a derivative of the well-established model for a conventional projectile used by McCoy. 30 Subscript F denotes the forward section and subscript A denotes the aft section.…”
Section: Projectile Dynamicsmentioning
confidence: 99%
“…e allowable maximum amplitude of projectile angle of attack is referenced to control the angle of attack increment produced by correction action, and controlling the angle of attack increment does not exceed the limited allowable value ∆δ max . According to (10) and (11), projectile motion state changes after correction. A change in each parameter is obtained:…”
Section: Control Of the Air Valve Working Pulse Width ∆Tmentioning
confidence: 99%
“…e stable flight of the projectile is controlled by limiting the pulse impulse as well as the distance between the pulse and the mass center. Wernert et al [8][9][10] studied the stability of canard-guided dual-spin stabilized projectiles.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the installation of a fuze with an infrared image sensor can not only improve attack accuracy, but also meet different mission requirements, which has received much attention. Li [2][3][4] proposed a novel trajectory correction fuze based on an image sensor. Then, the correction strategy of mortars was studied to improve the attack accuracy.…”
Section: Introductionmentioning
confidence: 99%